Study on gene expression in the liver at various developmental stages of human embryos - Chen, Hanqing; Li, Tingting; Cai, Ming; Huang, Zhiqi; Gao, Jianjun; Ding, Hongping; Li, Minmin; Guan, Weiyu; Chen, Jinpeng; Wang, Wenran; Li, Chunhong; Shi, Jianwu (Frontiers in Cell and Developmental Biology, 2025)
BackgroundThe normal development of the liver during human embryonic stages is critical for the functionality of the adult liver. Despite this, the essential genes, biological processes, and signal pathways that drive liver development in human embryos remain poorly understood.MethodsIn this study, liver samples were collected from human embryos at progressive developmental stages, ranging from 2-month-old to 7-month-old. Highly expressed genes and their associated enrichment processes at various developmental stages of the liver were identified through transcriptomic sequencing.ResultsThe findings indicated that genes associated with humoral immune responses and B-cell-mediated immunity were highly expressed during the early developmental stages. Concurrently, numerous genes related to vitamin response, brown adipocyte differentiation, T cell differentiation, hormone secretion, hemostasis, peptide hormone response, steroid metabolism, and hematopoietic regulation exhibited increased expression aligned with liver development. Our results suggest that the liver may possess multiple functions during embryonic stages, beyond serving hematopoietic roles. Moreover, this study elucidated the complex regulatory interactions among genes involved in lymphocyte differentiation, the regulation of hemopoiesis, and liver development. Consequently, the development of human embryonic liver necessitates the synergistic regulation of numerous genes. Notably, alongside conventionally recognized genes, numerous previously uncharacterized genes involved in liver development and function were also identified.ConclusionThese findings establish a critical foundation for future research on liver development and diseases arising from fetal liver abnormalities.